Mitral Valve Prolapse, Ventricular Arrhythmias, and Sudden Death. Issue 11 (10th September 2019) - Basso, Cristina; Iliceto, Sabino; Thiene, Gaetano; Perazzolo Marra, Martina
Abstract : Despite a 2% to 3% prevalence of echocardiographically defined mitral valve prolapse (MVP) in the general population, the actual burden, risk stratification, and treatment of the so-called arrhythmic MVP are unknown. The clinical profile is characterized by a patient, usually female, with mostly bileaflet myxomatous disease, mid-systolic click, repolarization abnormalities in the inferior leads, and complex ventricular arrhythmias with polymorphic/right bundle branch block morphology, without significant regurgitation. Among the various pathophysiologic mechanisms of electrical instability, left ventricular fibrosis in the papillary muscles and inferobasal wall, mitral annulus disjunction, and systolic curling have been recently described by pathological and cardiac magnetic resonance studies in sudden death victims and patients with arrhythmic MVP. In addition, premature ventricular beats arising from the Purkinje tissue as ventricular fibrillation triggers have been documented by electrophysiologic studies in MVP patients with aborted sudden death. The genesis of malignant ventricular arrhythmias in MVP probably recognizes the combination of the substrate (regional myocardial hypertrophy and fibrosis, Purkinje fibers) and the trigger (mechanical stretch) eliciting premature ventricular beats because of a primary morphofunctional abnormality of the mitral valve annulus. The main clinical challenge is how to identify patients with arrhythmic MVP (which imaging technique and in which patient) and how to treat them to prevent sudden death. Thus, there is a necessity for prospective multicenter studies focusing on the prognostic role of cardiac magnetic resonance and electrophysiologic studies and on the therapeutic efficacy of targeted catheter ablation and mitral valve surgery in reducing the risk of life-threatening arrhythmias, as well as the role of implantable cardioverter defibrillators for primary prevention. Abstract : Supplemental Digital Content is available in the text.